Literature Review: Formulation of Work-Life Balance Against Environmental Dynamics - Putra, Surya Jaya Purnama; Ratnawati, Tri; Santi, Dyan Evita (Yayasan Minang Darussalam, 2023)
The purpose of study This is For discuss possible strategies and formulations help individual reach balance life Work in face change sustainable environment changed . Research methods This use studies literature For analyze work-life balance based on study previously. Several strategies and formulations For increase balance life Work including flexibility time and place work , reduce demands work, use appropriate technology, develop habit life healthy, and get support from family and friends . In facing the dynamics change environmental , factors like technolog, demands work, and health must noticed For reach balance life healthy work. With apply appropriate strategies and formulations , individually can reach healthy balance between work and life personal.